Objectively measured physical activity and sedentary behaviour in children with bronchiectasis: a cross-sectional study - Joschtel, Barbara (BMC Pulm Med, 2019)
BACKGROUND: Bronchiectasis is a major contributor to respiratory morbidity and health care utilization in children and youth. Current treatment guidelines for bronchiectasis recommend participation in regular physical activity (PA) to improve aerobic fitness and quality of life (QoL). However, no previous study has assessed physical activity and sedentary behavior in this patient group, and the extent to which children with bronchiectasis meet guidelines for PA is unknown. In the absence of such data, we objectively measured the PA of children with bronchiectasis and compared them to current guidelines. METHODS: Forty-six children with bronchiectasis between 4 to 14 years (mean age 7.5 ± 2.6 years) were recruited from the Queensland Children’s Hospital, Brisbane. Daily time in sedentary, light, and moderate-to-vigorous PA (MVPA) was measured objectively over 7 days using the ActiGraph GT3X+ accelerometer and compared their values to current guidelines (minimum 60 min of MVPA daily). Compliance with the daily guideline and average daily steps counts were compared to normative data from two population–based health surveys of healthy children. RESULTS: We had complete measurements from 36 children. On average, they accumulated 48.6 min of MVPA daily and were sedentary for ~ 7 h/day. There was no statistical difference in these values between sexes or weekdays vs. weekends. Only 2 (5.6%) children met the 60-min daily MVPA recommendation compared to 42.1% of healthy children. Children with bronchiectasis accumulated 8229 steps/day (boys: 8422 ± SD 473, girls: 8037 ± 594), well below the recommended 12,000 steps/day. In comparison, daily step counts in healthy children ranged from 11,500–14,500 steps/day. CONCLUSION: Children with bronchiectasis are insufficiently active for health benefit and would substantially benefit from programs to promote PA and reduce sedentary behavior.